ОЛИЙ ЎҚУВ ЮРТИ ТАЛАБАЛАРИНИНГ ИЖОДИЙ ФАОЛЛИГИНИ ШАКЛЛАНТРИШДА МЕДИАКОМПЕТЕНТЛИКНИНГ РОЛИ - Қыдырниязов, А. (SCIENCE and SOCIETY, 2017)
In the article the issue of formation of creative activity of students of higher educational institutions is considered. It is shown that media competence and its development plays an important role in the formation of creative activity of students.
Keywords: creative activity; ICT competence; media education; media literacy; media text; mediacompetence